Jenis-Jenis Insiden Keselamatan Pasien di Pusat Kesehatan Masyarakat - Shinta Nuria; Inge Dhamanti (Universitas Airlangga, 2023)
Background: Developing a patient safety culture in the public health center is less significant than in hospitals. According to WHO, primary care services can prevent up to 80% of injuries, which accounts for half the global burden of patient injury. Objectives: This study aims to determine the type of patient safety incidents in public health centers in Surabaya. Methods: This research is classified as descriptive-analytic research with a cross-sectional research design, used secondary data collected through the monthly reports of